STUDY OF INTERNAL SOLITARY WAVES FEATURE EXTRACTION BASED ON STATIONARY WAVELET TRANSFORM BY SENTINEL-1A IMAGE IN LOMBOK STRAIT - Chonnaniyah Chonnaniyah; Takahiro Osawa; I Wayan Gede Astawa Karang (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2019)
Stationary Wavelet Transform (SWT), mother function Symlet 4, shows an effective method for Internal Solitary Waves (ISW) feature extraction and four parameters (soliton numbers, first crest length, wavelength and propagation direction) estimation by Sentinel-1A C-band Synthetic Aperture Radar (SAR) imagery in Lombok Strait. The ISW feature can be distinguished from other features using the SWT noise reduction process and simple thresholding methods. ISW feature extraction results by SAR images can show ISW characteristics more clearly and can be used as a basis for obtaining ISW spatial-temporal distribution maps in the Lombok Strait. Our estimation results show that the arc-like type of ISW in the Lombok Strait propagated to the north of the sill with the detected soliton numbers are 2 solitons per packets with a wavelength about 3.20 km and the first crest length varies about 60.27 km near the Kangean Island with the propagation direction about 50.38 degree to the North.